Risk Factors of Mortality From Pneumocystis Pneumonia in Non-HIV Patients: A Meta-Analysis - Wang, Yuqiong; Zhou, Xiaoyi; Saimi, Maidinuer; Huang, Xu; Sun, Ting; Fan, Guohui; Zhan, Qingyuan (Frontiers in Public Health, 2021)
Background: To systematically review the risk factors of mortality from non-HIV-related Pneumocystis jirovecii pneumonia (PCP) to provide the theoretical basis for managing non-HIV-related PCP. Methods: PubMed, Embase, Web of Science, the Cochrane Library and CNKI databases were searched. A meta-analysis of the risk factors of mortality from non-HIV-related PCP from the included studies was conducted. Results: A total of 19 studies and 1,310 subjects were retrieved and included in the meta-analysis, including 485 and 825 patients in the non-survivor and survivor groups, respectively. In the primary analysis, age, pulmonary disease, solid tumors, cytomegalovirus co-infection, lactate dehydrogenase, lymphocyte count, invasive ventilation during hospitalization, and pneumothorax were associated with mortality from non-HIV-related PCP, whereas sex, albumin, PCP prophylaxis, use of corticosteroids after admission, and time from onset of symptoms to treatment were not associated with mortality from non-HIV-related PCP. Conclusions: The mortality rate of non-HIV-infected patients with PCP was still high. Age, pulmonary disease, solid tumors, cytomegalovirus co-infection, lactate dehydrogenase, lymphocyte count, invasive ventilation during hospitalization, and pneumothorax were risk factors of mortality from non-HIV-related PCP. Improved knowledge of prognostic factors is crucial to guide early treatment.